Factores que influyen en el nivel de cumplimientode la lista de chequeo de cirugía segura en elHospital San Juan de Lurigancho, 2017 - Condor Rios, Ruth (2017)
Objective: To determine the factors that Influence on the Level of Compliance of the surgical safety checklist in the Surgical Center in San Juan de Lurigancho Hospital, 2017. Materials and Methods: The research was descriptive and analytical. The design was non-experimental and cross-sectional. The sample included 20 nurses in the Surgical Center in San Juan de Lurigancho Hospital. Two instruments were developed according to the factors and according to the level of compliance. A Likert scale and a dichotomous scale respectively. Results: Statistical analysis was performed, within the findings, it was found that the factors that influence on the level of compliance of the surgical safety checklist in the Surgical Center in San Juan de Lurigancho Hospital were the administrative and technological factors, so rejecting the proposed hypothesis. Conclusion: The administrative and technological factors influence in a significant way on the level of compliance of the surgical safety checklist in the Surgical Center in San Juan de Lurigancho Hospital.